Role of serum bilirubin as a marker of acute gangrenous appendicitis - Ghimire, P; Thapa, P; Yogi, N; Ghimire, P (Nepal Journal of Medical Sciences, 2012)
Background: This study has compared the difference in serum bilirubin between patients with gangrenous and non-gangrenous appendicitis. Methods: A prospective analytical study of, 141 patients who underwent appendectomy, from March 2010 to March 2011 in Manipal Teaching Hospital, Pokhara, Nepal was carried out. Clinico-demographic data, Alvarado’s score, total serum bilirubin, total leucocyte count and histopathological report of all the cases were collected in a prestructured proforma. Comparison between gangrenous and non-gangrenous appendicitis groups was carried out using independent sample t test, Chisquare test, and direct logistic regression. The data was analyzed using SPSS 11.6 software. Result: Around 43% (61 out of 141) patients had gangrenous appendicitis and statistically significant difference was found between the two groups in total Alvarado’s score, total count and total bilirubin level. The effect size as indicated by eta square statistics was large for total bilirubin (eta squared=0.39) as compared to total Alvarado’s score (0.09) and total leucocyte count (0.05). Direct logistic regression model showed serum total bilirubin as the only independent variable to make a unique statistically significant contribution in predicting gangrenous appendicitis. Conclusion: Pre-operative assessment of serum total bilirubin can serve as an important maker of acute gangrenous appendicitis. DOI: http://dx.doi.org/10.3126/njms.v1i2.6606 Nepal Journal of Medical Sciences. 2012;1(2): 89-92